Total Economic Value of Cattle Farming in Integrated Waste Disposal Sites Bantul Yogyakarta - Kusumastuti, Tri Anggraeni; Andarwati, Siti; Widiati, Rini (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 2 (2023): Vol 17 No 2 (2023)DO - 10.24843/SOCA.2023.v17.i02.p03, 2023)
Cattle rearing in the Integrated Waste Disposal Area brings environmental pollution and reduces the comfort of livestock. This study aims to identify the condition of the cattle rearing profile, measurement of business feasibility, and analysis of the Total Economic Value of cattle existing values. The research location is in Ngablak Hamlet, Sitimulyo Village, Piyungan District, Bantul, Yogyakarta. The time of the study from August to November 2019. Sampling of farmers by census was 52 farmers. Data analysis with quantitative descriptive method. The results showed that farmers prefer with semi-intensive types for rearing and Simpo breeds. The biggest income is semi-intensive. Sustainability of cattle business is feasible from an economic and environmental if an intensive rearing is applied. If analyzed include the investment costs of feed, land, and cages, all maintenance systems are not feasible. The net benefit shows that if there is a cattle mortality, the farmer should be fined a minimum of that amount. Total Economic Value shows the value of cattle existing value assets in Ngablak Village annually. Overall, it is necessary to plan for shifting maintenance to an intensive system to maintain the existence and animal welfare of cattle as a resource input in the area